Tex. Penal Code ch. 14, arts. 611-12 (1857) - (:unkn) unknown (My University, 1856)
Provided that the use of a Bowie knife or a dagger in manslaughter is to be deemed murder.
Keywords: COMMITTING CRIME W/ WEAPON - NON-GUN ARMS